Cultivation of Thyrsopteris elegans - Ensoll, Andy; Matthews, Kate (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2004)
Thyrsopteris elegans Kunze is a monospecific genus of fern endemic to the Juan Fernandez Islands, off the coast of Chile. These islands have large numbers of alien invasive species and the native flora, including T elegans which already has a very restricted distribution, is consequently under considerable threat. One of the largest examples of this species in cultivation in Britain grows at the Royal Botanic Garden Edinburgh and this paper describes its propagationand cultivation.